Numerical modelling of the thermospheric and ionospheric effects of magnetospheric processes in the cusp region - A. A. Namgaladze; A. A. Namgaladze; A. N. Namgaladze; M. A. Volkov (Annales Geophysicae, 1996)
The thermospheric and ionospheric effects of the precipitating electron flux and field-aligned-current variations in the cusp have been modelled by the use of a new version of the global numerical model of the Earth's upper atmosphere developed for studies of polar phenomena. The responses of the electron concentration, ion, electron and neutral temperature, thermospheric wind velocity and electric-field potential to the variations of the precipitating 0.23-keV electron flux intensity and field-aligned current density in the cusp have been calculated by solving the corresponding continuity, momentum and heat balance equations. Features of the atmospheric gravity wave generation and propagation from the cusp region after the electron precipitation and field-aligned current-density increases have been found for the cases of the motionless and moving cusp region. The magnitudes of the disturbances are noticeably larger in the case of the moving region of the precipitation. The thermospheric disturbances are generated mainly by the thermospheric heating due to the soft electron precipitation and propagate to lower latitudes as large-scale atmospheric gravity waves with the mean horizontal velocity of about 690 m s–1. They reveal appreciable magnitudes at significant distances from the cusp region. The meridional-wind-velocity disturbance at 65° geomagnetic latitude is of the same order (100 m s–1) as the background wind due to the solar heating, but is oppositely directed. The ionospheric disturbances have appreciable magnitudes at the geomagnetic latitudes 70°–85°. The electron-concentration and -temperature disturbances are caused mainly by the ionization and heating processes due to the precipitation, whereas the ion-temperature disturbances are influence strongly by Joule heating of the ion gas due to the electric-field disturbances in the cusp. The latter strongly influence the zonal- and meridional-wind disturbances as well via the effects of ion drag in the cusp region. The results obtained are of interest because of the location of the EISCAT Svalbard Radar in the cusp region and the associated observations at lower latitudes that will be possible using the existing EISCAT UHF and VHF radars. The paper makes predictions for both these regions, and these predictions will be tested by joint observations by ESR, EISCAT UHF/VHF and other ground-based ionosphere/thermosphere observations.